Impact of bone marrow mononuclear cells therapy on left ventricular function in patients with ST-elevated myocardial infarction: A meta-analysis. Issue 16 (April 2018) - Wang, Chao; Han, Xiujiang; Li, Yongjian; Zhang, Boya
Abstract: Background: Bone marrow mononuclear cell (BMMNC) therapy has been used as an adjunctive treatment in patients with ST-elevated myocardial infarction (STEMI). However, the therapeutic efficacy of this approach remains controversial. The present meta-analysis is aimed to evaluate the impact of cell therapy on left ventricular function after STEMI. Methods: We searched through PubMed and EMBASE databases till 2017 for all relevant publications using certain search terms. Randomized controlled trials investigating the effect of BMMNC therapy in patients with STEMI who underwent percutaneous coronary intervention were selected. Wall motion score index (WMSI), infarct size, wall thickening, and myocardial perfusion were our endpoints. Results: A total of 24 trials with 1536 patients were included in our study. Overall, as observed in our data, cell therapy reduced infarct size by −2.32 (95% confidence interval [CI] −4.03, −0.62; P = .007; I 2 = 24%) and improved myocardial perfusion by −3.04 (95% CI −3.94, −2.15; P < .001; I 2 = 0%). However, there was no significant difference between treatment group and control group in WMSI or wall thickening. Conclusion: Intracoronary BMMNC infusion is safe for patients with STEMI. It is also associated with improvement of infarct size and myocardial perfusion. Further multicenter randomized trials should be conducted to validate the therapeutic efficacy of this treatment.